2020
DOI: 10.1101/2020.03.09.984187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pesticide contamination of milkweeds across the agricultural, urban, and open spaces of low elevation Northern California

Abstract: 22Insects are facing multifaceted stressors in the Anthropocene and are in decline in many parts of 23 the world. The widespread use of pesticides is believed to be an important part of the problem. In 24 particular, the monarch butterfly is in sharp decline in the western United States. Here we show 25 that milkweeds in the Central Valley of California, a large urban and agricultural landscape that 26 is part of the monarch breeding and migration route, are contaminated with a diverse array of 27 pesticides. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Overall, our data point to several key messages. First, based on the results from this experiment combined with several other recently published studies 45,47,52,75 , it seems unlikely that neonicotinoids are one of the primary drivers of monarch declines. This is not to say that neonicotinoids are completely innocuous, but compared with other ongoing threats (e.g., loss of milkweed host-plants and overwintering habitat), they likely play a secondary role.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Overall, our data point to several key messages. First, based on the results from this experiment combined with several other recently published studies 45,47,52,75 , it seems unlikely that neonicotinoids are one of the primary drivers of monarch declines. This is not to say that neonicotinoids are completely innocuous, but compared with other ongoing threats (e.g., loss of milkweed host-plants and overwintering habitat), they likely play a secondary role.…”
Section: Discussionmentioning
confidence: 75%
“…Although we did not directly test this compound, its toxicity to monarchs is comparable to clothianidin and several orders of magnitude less than more potent insecticides like beta-cyfluthrin (pyrethroid) and chlorantraniliprole (anthranilic diamide) 45 . A recent field survey of pesticide contamination in western US milkweeds similarly concluded that chlorantraniliprole was a far greater threat to monarchs than neonicotinoids 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little research has been done on the impact of neonicotinoids on butterflies. They are known to kill Monarch butterflies in the laboratory (42), and lethal quantities have been found in host plants in the field (43). Harmful effects have also been shown for predators of butterflies and other insects (44).…”
Section: Causes Of Declinementioning
confidence: 99%
“…Plant protection products (PPPs, e.g., pesticides and herbicides) associated with agriculture pose a second threat. Apart from imminent mortal effect after acute exposure, the larval performance, species richness, and abundance are also affected by chronical exposure [ 65 , 66 , 67 , 68 , 69 , 70 ]. Therefore, butterflies often suffer collateral damage under broad-spectrum pesticides in either agroecosystems or artificial green space in urban areas [ 2 , 71 , 72 , 73 ].…”
Section: China’s Butterfly Diversity and Threatsmentioning
confidence: 99%